Morphological Diversity of Local Sorghum Cultivar (Sorghum bicolor) of East Nusa Tenggara, Indonesia - Tnunay, Ite Morina Yostianti; Chikmawati, Tatik; Miftahudin, Miftahudin (Biosaintifika: Journal of Biology & Biology Education, 2019)
Sorghum has great potential to be developed in marginal lands of Indonesia including East Nusa Tenggara. However, the information about sorghum diversity in this area was very limited. This research aimed to describe morphological variation, and assessing the value of genetic diversity based on morphological characters of local sorghum cultivar of East Nusa Tenggara. The exploration and sample collection were conducted in 3 islands, i.e.: Timor, Sumba, and Flores. The observation of morphological characters was based on sorghum descriptor. Morphological character similarities were analyzed using Simple Matching (SM) coefficient, and a dendrogram was constructed using Unweighted Pair Group Method with Arithmetic Average (UPGMA) method. The results showed that 36 accessions of sorghum in East Nusa Tenggara varied in 17 morphological characters. At the similarity coefficients of 48%, all sorghum accessions were separated into 2 groups based on the presence or absence of aleurone layer. Group I consisted of 12 accessions with no aleurone layer, while group II consisted of 24 accessions has aleurone layer. The genetic diversity of sorghum of East Nusa Tenggara is low (I=0.62–0.71 and h=0.37-0.42). The genetic diversity between populations (HT=0.4203) is higher than within populations (HS=0.3961). This study provides the first complete information about sorghum diversity in East Nusa Tenggara that will be useful as basic information for sorghum development in this area in the future.